Interactive Peacemaking A People-Centered Approach - Allen, Susan H. (Routledge Studies in Peace and Conflict Resolution, 2022)
This book examines the theory and practice of interactive peacemaking, centering the role of people in making peace. The book presents the theory and practice of peacemaking as found in contemporary processes globally. By putting people at the center of the analysis, it outlines the possibilities of peacemaking by and for the people whose lives are touched by ongoing conflicts. While considering examples from around the world, this book specifically focuses on peacemaking in the Georgian-South Ossetian context. It tells the stories of individuals on both sides of the conflict, and explores why people choose to make peace, and how they work within their societies to encourage this. This book emphasizes theory built from practice and offers methodological guidance on learning from practice in the conflict resolution field. This book will be of much interest to students and practitioners of peacemaking, conflict resolution, South Caucasus politics and International Relations.